Attitude to change and tolerance to uncertainty as predictors of adaptability and adaptive readiness - Rail М. Shamionov (Rossijskij psihologičeskij žurnal., 2018)
Introduction. Studying the determinants of socio-psychological adaptability and adaptive readiness, as well as their relationship, is an important issue of recent research. This study presents new data on predictors and the level of prediction of the person’s adaptability and adaptive readiness, the structural model with the ways for readiness to change, adaptation, the attitude to uncertain situations, and the person’s adaptability. Methods. The study used the following techniques: (a) the estimation of the characteristics of tolerance to uncertainty by D. McClane in E. N. Osin’s modification; (b) the technique for diagnostics of socio-psychological adaptability by K. Rogers and R. Diamond in A. K. Osnitsky’s modification; (c) the developed original scales for the assessment of adaptive readiness and readiness to change. The study involved 75 women and men (men – 38 %, mean age – 26.8 years). Results and Conclusion. The study presented the classification of the original set of parameters into groups and associations between them. Adaptive readiness, readiness to change, tolerance to uncertainty, and adaptability form a united symptom complex with complex cross-functional interrelations. On the basis of structural modeling the study revealed the ways for readiness to change, adaptation, the attitude to uncertain situations, and the person’s adaptability. In conclusion: readiness to change mediates the relationship between adaptive readiness and the attitude to uncertainty. Adaptability, adaptive readiness and the attitude to uncertainty form a circular relationship. Socio-demographic characteristics form a complex of predictors of socio-psychological adaptability. They are not associated with adaptive readiness. The attitude to uncertainty reduces socio-demographic determination and plays a significant role in the formation of the person’s adaptability.